Secreção de insulina, sinalização de Ca2+ e função mitocondrial em ilhotas de ratas senescentes - Coelho, Fernanda Monteiro [UNIFESP] (2010)
Aging is associated with changes in pancreatic β cells sensitivity to nutrients resulting in glucose intolerance and diabetes mellitus (DM) type 2 (DM 2) development. Here the study cells function Ca2+ signaling, mitochondrial morphophysiology and redox state of isolated islets from senescent rats with 24-25 months old. Adult rats wister 4-5 months old were used as controls. Islets from senescent rats secreted less insulin in the presence of glucose. The influx of Ca2+ in response to depolarization is smaller in senescent islets when compared to adult islets. Also, the increase in insulin secretion induced by the cholinergic agent carbachol (Cch) was lower in the senescent islets. In addition, from senescent rats showed lower NAD (P) H production in response to glucose, decreased mitochondrial electric potential (ΔΨm) and a higher accumulation of the reactive oxygen species (ROS) when compared to islets from adult rats. Electron microscopy showed that the β cells from senescent islets presented higher lysosomes and residual bodies density, and changes in the morphology of the mitochondria, that showed alterations in the mitochondrial cristae when compared to adult group. Furthermore, nuclear invaginations were observed in cells of senescent group indicate apoptosis in this group. However, the rate of apoptosis analysed by TUNEL methodology showed no changes between the groups. In conclusions, the secretory capacity of the pancreatic β cells in the presence of glucose and the cholinergic stimulation were decreased in aging, these effects were associated with related mitochondrial morphophysiology dysfunction that result in decreased metabolism and increased ROS production. These effects together with the lower Ca2+ influx in response to depolarization and lower potentiation of the secretion in repose to the colinergic stimulus, results a diruption on the β cells stimulus/secretion coupling.